2015
DOI: 10.1016/j.pain.0000000000000017
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic surgery and bone fracture pain are both significantly attenuated by sustained blockade of nerve growth factor

Abstract: The number of patients suffering from postoperative pain due to orthopedic surgery and bone fracture is projected to dramatically increase because the human life span, weight, and involvement in high-activity sports continue to rise worldwide. Joint replacement or bone fracture frequently results in skeletal pain that needs to be adequately controlled for the patient to fully participate in needed physical rehabilitation. Currently, the 2 major therapies used to control skeletal pain are nonsteroidal anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 72 publications
(83 reference statements)
0
54
1
Order By: Relevance
“…In other orthopedic surgery animal models (i.e., femoral pin placement and fracture or fracture with casting), spontaneous, palpation-induced nocifensive behaviors and mechanical allodynia were observed (50,51), contrasting our results where mice did not display secondary tactile allodynia after tibial fracture with intramedullary pinning. For example, Guo et al (51) reported mechanical allodynia in rats using von Frey filaments after distal tibial fracture with a cast, but only monitored behavior at a chronic stage (4 wk after surgery).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In other orthopedic surgery animal models (i.e., femoral pin placement and fracture or fracture with casting), spontaneous, palpation-induced nocifensive behaviors and mechanical allodynia were observed (50,51), contrasting our results where mice did not display secondary tactile allodynia after tibial fracture with intramedullary pinning. For example, Guo et al (51) reported mechanical allodynia in rats using von Frey filaments after distal tibial fracture with a cast, but only monitored behavior at a chronic stage (4 wk after surgery).…”
Section: Discussioncontrasting
confidence: 99%
“…For example, Guo et al (51) reported mechanical allodynia in rats using von Frey filaments after distal tibial fracture with a cast, but only monitored behavior at a chronic stage (4 wk after surgery). For nocifensive behavior in a femoral pin placement and fracture model, Majuta et al (50) gently and repeatedly pressed, with thumb and forefinger, the thigh of the fractured hind limb for 2 min. This is different from our protocol of carrying out the von Frey filament test no later than 2 wk after fracture, when the leg is not completely stable (50,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Data is presented as percent weight borne by ipsilateral hindlimb over the total weight borne by both hindlimbs. Dynamic weight bearing was performed as previously described [42; 53; 62]. …”
Section: Methodsmentioning
confidence: 99%
“…Using this approach we found that anti-P2X3 significantly reduced hypersensitivity of skin, but had no significant effect on attenuating skeletal pain-related behaviors. In contrast, anti-NGF, which has been shown to reduce skeletal pain in both humans and animals models [16; 21; 28; 30; 35; 36; 38; 42; 46; 54; 57], attenuated both mechanical hypersensitivity of the skin and skeletal pain-related behaviors. These results suggest that therapies that attenuate skeletal pain-induced skin hypersensitivity may not always predict therapies that also attenuate the underlying skeletal pain.…”
Section: Introductionmentioning
confidence: 99%
“…Both these therapies have also been shown to slow the growth of a wide variety of cancers and are commonly used as a first line therapy to treat CIBP 3,11,21,22,45,48 . Additionally, at least in preclinical models, anti-NGF therapy has also been shown to reduce the growth of head and neck cancer as well as reducing tumor-induced bone remodeling and time to fracture in a mouse model of bone cancer pain 30,52,79,97 .…”
Section: Discussionmentioning
confidence: 99%